FRI0080 The role of pain in rheumatoid arthritis (RA) patients' assessments of their health. (12th June 2018) - Katz, P.; Lee, Y.C.; Quebe, A.; Sun, L.; Patel, H.; Gaich, C.; Boytsov, N.; Michaud, K.
Abstract : Background: Patients often describe pain as the most important symptom of RA. Despite advances in RA therapy to improve disease control, some patients continue to have significant pain 1, 2 . The relative impact of pain on RA patients' evaluations of overall health and RA-specific global assessments is unknown. Objectives: Determine the relative role of pain in RA patients' health assessments. Methods: Data derived from the Forward (The National Databank for Rheumatic Diseases) longitudinal cohort, collected January-May 2017. Respondents (n=5471) have rheumatologist-confirmed RA. Two health assessments were examined: 1 overall satisfaction with health (SAT) measured by the item: "How satisfied are you with your health now?" with responses of very unsatisfied to very satisfied; and 2 patient global assessments of RA impact (GBL) measured using a numeric rating scale (NRS): "Considering all the ways that your RA affects you, rate how you are doing on a scale of 0–10, where 0=very well and 10=very poor." For regression analyses, SAT was dichotomized as "very satisfied" or "somewhat satisfied" vs. other responses. Current pain severity was rated on an NRS from 0 (no pain) to 10 (extreme pain). Spearman correlations examined the association of pain with SAT and GBL. Initial multiple regression analyses (table 1, Model 1) examined the following as predictors of SAT and GBL: age, sex, education, disease duration, obesity (BMI ≥30), conventional and biologic DMARD use, Rheumatic Disease Comorbidity Index 3 (RDCI), self-report of depression, fatigue, and functional limitations (Health Assessment Questionnaire [HAQ] score). Follow-up models (Model 2) added pain to determine its relative independent role in health assessments. Results: The sample was 84% female, mean age 65 years, mean RA duration 22 years. 53% were satisfied with their health, and mean GBL was 3.6±2.5. Mean pain severity rating was 3.8±2.8. Correlations of pain with SAT and GBL were 0.58 and 0.71, respectively (each p<0.0001). Regression models predicting both SAT and GBL improved with the addition of pain (table 1). Pain was significantly and independently associated with both health assessments. Regression models included age, sex*, education, disease duration, obesity, medications, RDCI, depression, fatigue*, and HAQ*. Variables noted with asterisk were also statistically significant (p<0.05) in both final models. Conclusions: Pain plays a critical role in RA patients' assessments of general and RA-specific health. Analyses suggest that pain may be more important to RA global assessments than to overall health satisfaction, though the clinical relevance of this difference is not known. RA global assessments are included in some indices of disease activity. Future research should focus on distinguishing between non-inflammatory and inflammatory causes, which may lead to more accurate assessment of RA disease activity. References: [1] Lee YC, et al. Arthritis Res Ther2011;13:R83. [2] Altawil R, et al. Arthritis Care Res2016;68:1061. [3] England BR. Arthritis Care Res2015;6:865. Disclosure of Interest: P. Katz Grant/research support from: Eli Lilly and Co, Y. Lee Grant/research support from: Eli Lilly and Co, A. Quebe Employee of: Eli Lilly and Co, L. Sun Employee of: Eli Lilly and Co, H. Patel Employee of: Eli Lilly and Co, C. Gaich Employee of: Eli Lilly and Co, N. Boytsov Employee of: Eli Lilly and Co, K. Michaud Grant/research support from: Eli Lilly and Co